Diarrhea and acaroid mites: A clinical study - Li, Chao-Pin (World J Gastroenterol, 2003)
AIM: To explore the characteristics of diarrhea caused by acaroid mites. METHODS: Acaroid mites in fresh stools of 241 patients with diarrhea were separated by flotation in saturated saline. Meanwhile, skin prick test, total IgE and mite-specific IgE were detected in all patients. RESULTS: The total positive rate of mites in stool samples of the patients was 17.01% (41/241), the positive rates of mites in male and female patients were 15.86% (23/145) and 18.75% (18/96), respectively, without significant difference (P > 0.05). The percentage of skin prick test as" +++", "++", "+", and "-" was 9.13% (22/241), 7.47% (18/241), 5.81% (14/241), 4.98% (12/241) and 72.61% (175/241), respectively. The serum levels of total IgE, mite-specific IgE in patients with and without mites in stool samples were (165.72 ± 78.55) IU/ml, (132.44 ± 26.80) IU/mL and (145.22 ± 82.47) IU/ml, (67.35 ± 45.28) IU/ml, respectively, with significant difference (P < 0.01). The positive rate of mites in stool samples in staffs working in traditional Chinese medicine storehouses or rice storehouses (experimental group) was 26.74% (23/86), which was significantly higher than that (11.61%, 18/155) in people engaged in other professions (χ(2) = 8.97, P < 0.01). CONCLUSION: Acaroid mites cause diarrhea and increase serum levels of total IgE and mite-specific IgE of patients, and the prevalence of diarrhea caused by acaroid mites is associated with occupations rather than the gender of patients.